2022
DOI: 10.3390/pharmaceutics14030496
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention of Urothelial Cell Carcinoma Tumorigenesis by Dietary Flavokawain A in UPII-Mutant Ha-ras Transgenic Mice

Abstract: Non-muscle-invasive bladder cancer (NMIBC) has one of the highest recurrence rates among all solid cancers and the highest lifetime treatment cost per patient. Therefore, the development of chemoprevention strategies for reducing the occurrence and recurrence of NMIBC as well as its burdens on the healthcare system is valuable. Our aim was to determine whether flavokawain A (FKA), a kava chalcone isolated from the kava plant, can target the in vivo activated Ha-ras pathway for prevention and treatment of NMIBC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…Therefore, CSCs have been considered as a driver for cancer initiation, progression, metastasis, drug resistance, and recurrence (3,14,16). We have demonstrated that FKA, a novel chalcone from the kava plant, inhibits the growth of bulk tumor cells in different transgenic models and xenograft tumor models (6)(7)(8)23). The bulk of tumors consists of heterogenous cell populations, including non-CSCs and CSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, CSCs have been considered as a driver for cancer initiation, progression, metastasis, drug resistance, and recurrence (3,14,16). We have demonstrated that FKA, a novel chalcone from the kava plant, inhibits the growth of bulk tumor cells in different transgenic models and xenograft tumor models (6)(7)(8)23). The bulk of tumors consists of heterogenous cell populations, including non-CSCs and CSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Zi et al recognized FKA as a major component in kava and showed that it had a major effect on inhibiting BC tumorigenesis (Figs. 3c) [30]. We tested the effective dose of three kava extracts, FKA, FKB, and FKC, and found that BC cells were most sensitive to FKA (Figs.…”
Section: Evaluation Of Fka As a Candidate Drug For Targeting Prmt5mentioning
confidence: 99%
“…In addition, FKA could induce a G2-M arrest in the bladder and prostate cancer cells [28,29]. In mouse models, FKA targeted the activated Ha-Ras pathway for the prevention and treatment of non-muscle invasive BC [30]. FKA is not metabolized by the liver, but is mainly concentrated in urine, indicating that orally administrated FKA could specifically act on urinary tract carcinoma [28].…”
Section: Introductionmentioning
confidence: 99%
“…The male homozygous UPII-mutant Ha-ras transgenic model allows us to study the effect of an agent on the survival (one of the most important endpoints for cancer prevention and treatment) of bladder tumor-bearing mice in a feasible way. Molecularly, the UPII-mutant Ha-ras transgenic model mirrors high mTOR activity, which presents in approximately 70% of human urinary bladder cancer [ 6 , 7 , 8 , 9 ]. The mTOR pathway regulates aerobic glycolysis, and then rewires the metabolic programs of the tumor cells to promote cell proliferation [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mTOR pathway regulates aerobic glycolysis, and then rewires the metabolic programs of the tumor cells to promote cell proliferation [ 10 ]. Therefore, the male homozygous UPII-mutant Ha-ras transgenic model is currently the most suitable model for examining the preventive and treatment effects of novel agents on bladder cancer metabolism and recurrence progression [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%